The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.47278/journal.abr/2020.003
|View full text |Cite
|
Sign up to set email alerts
|

Avian Coccidiosis: Recent Advances in Alternative Control Strategies and Vaccine Development

Abstract: Coccidiosis induces huge economic losses to poultry production. Its control through anticoccidial live vaccines and drugs has been very successful with some limitations because of the cost of production of live vaccines, drug resistance, and residues representing public health concerns. Consequently, there is a crucial need for drug-free production of foods. Useful strategies include environmental, immunological, and genetic approaches; feed additives are recent attitudes involving probiotics, synbiotics, orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 97 publications
(115 reference statements)
0
32
0
Order By: Relevance
“…Huge economic losses are rendered by the Brucellosis (Shahzad et al 2018), especially in food animal production sector. The economic losses in animals due to Brucellosis are primarily due to abortions, occurring during the last trimester, decreased milk yield, transient infertility and perinatal mortalities (Gul et al 2015;Zeng et al 2019;Khan et al 2020). The disease is endemic in the buffalo and cattle, causing approximate economic loss of US $ 344 billion to the animal industry (Pal et al 2020).…”
Section: History Spread and Pathogenmentioning
confidence: 99%
See 1 more Smart Citation
“…Huge economic losses are rendered by the Brucellosis (Shahzad et al 2018), especially in food animal production sector. The economic losses in animals due to Brucellosis are primarily due to abortions, occurring during the last trimester, decreased milk yield, transient infertility and perinatal mortalities (Gul et al 2015;Zeng et al 2019;Khan et al 2020). The disease is endemic in the buffalo and cattle, causing approximate economic loss of US $ 344 billion to the animal industry (Pal et al 2020).…”
Section: History Spread and Pathogenmentioning
confidence: 99%
“…Brucellosis causes abortion, reduced fertility, decreased milk production and cost of replacement (Khan and Zahoor 2018). Serious socioeconomic issues can be posed by the disease to livestock owners (Khan et al 2020). Due to rapidly increasing intercontinental tourism and animal trade, there are high chances that the disease could spread in developed countries (Imtiaz et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the market oriented dairy farming, calves are mostly separated from their dams and reared separately (Khan et al, 2020 andDe Rosa et al, 2017) and the priority of selling more milk, instead of feeding to calves is in practice (Iqbal et al, 2014 andCantor et al, 2019). Previous research reported that the nutritional component of the dam and calf bond is essential for better growth and production (Mandel and Nicol, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…When the calf is suckled the residual milk after milking, it increased degree of udder emptying and enhances production (Sandoval-Castro et al, 2000). The natural nursing of calves depends on the development of social bonds with the dam and it is necessary for the survival and welfare of newborn calf (Enriquez et al, 2010 andKhan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In India and Africa, serotypes B:2 and E:2, respectively are responsible for causing HS in large ruminants [3], although serotypes A:1 and A:3 have also been linked. HS affected buffalo exhibit respiratory sounds, profuse salivation, dyspnoea, mucous nasal discharge, high temperature, reduced appetite, restlessness, mandibular and neck region oedema, and redness [4]. According to 19 th livestock census (2012), the total bovine population was 299.9 million in India (http://dahd.nic.in/sites/default/filess/Livestock%20 %205_0.pdf).…”
Section: Introductionmentioning
confidence: 99%